Preparation and Characterization of Some Metal Complexes with New Heterocyclic Schiff-Azo Ligand - Mahdi, Raheem T; Ali, Abid Allah M; Noaman, Huda A (Al-Nahrain Journal of Science, 2018)
Chelation complexes of Cu(II), Hg(II), Zn(II) Ni(II) Co(II) Cd(II) were prepared with new heterocyclic Schiff azo ligand (E)-N-(1-(4-((E)-(4,5-diphenyl-1H-imidazol-2-yl) diazenyl) phenyl) ethylidene)-4-methylaniline. This ligand was synthesized and characterized by IR spectra, U.V–visible spectra, (C.H.N) analysis and its complexes were characterized by flame atomic absorption, molar conductivity and magnetic moment. It was found that the Schiff azo ligand behaves as a neutral bidentate (N,N΄) ligand forming chelates with (1: 2) (metal: ligand) stoichiometry. Depending upon all results was proposed an octahedral geometry for the complexes.